TINGKAT KECUKUPAN CAIRAN PADA PASIEN GANGGUAN JIWA DI RUMAH SAKIT dr. H. MARZOEKI MAHDI BOGOR - Sujanawan, Mochamad Enra; Riyadi, Hadi (Jurnal Gizi dan Pangan, 2014)
The purpose of this study was to measure the fluids adequacy of mental disorder patients. This study was a cross-sectional study at dr. H. Marzoeki Mahdi hospital in Bogor. The number of subjects were 13 mental disorder patients at a condition of calm and willing to collaborate in data collection body weight, height and consumption for three days. Overall fluids requirement of the total subject was 2 376.39±199.80 mL/day. Mean fluid intake from food, drink and metabolic at the patients were 2 530.78±856.02 mL/day. The fluids adequacy of males were 102.83±8:24%, while the females were 116.90±17.80%. Fluids adequacy in patients were 76.92% categorized as enough and 23.08% categorized as excessive.